Institutional Export Barriers on Exporters from Emerging Markets: Evidence from China - Jia Li (Advances in Theory and Practice of Emerging Markets, 2018)
The emerging markets have become the increasingly important trading nations in the global economy. Given its significance to practitioners and policymakers, export barriers has been the popular topic in the international business studies. However, research about export barriers caused by the local institutions are under developed, though institutional voids and institutional inefficiency are reported as the major determinants for business development in emerging markets. This paper aims to fill in this gap by exploring the institutional export barriers in emerging markets. Based on existing studies on export barriers and institutional perspective, a conceptual framework is initially developed by separating formal and informal institutional export barriers. Then three specific institutional export barriers are identified, including government policy, weak legal system and informal and personal networks. In the meanwhile, this paper sheds light on how the institutional export barriers are developed and obstruct exporting in emerging markets.